2011
DOI: 10.1007/s10311-011-0310-x
|View full text |Cite
|
Sign up to set email alerts
|

Strong adsorption of DNA molecules on humic acids

Abstract: Analysing soil microbial communities is often hampered by DNA adsorption on soil organic compounds such as humic acids. However the role of humic acids in DNA adsorption and stability in soils remains controversial. To characterize DNA-humic acid interactions, we studied DNA adsorption on two commercially available humic acids and a soil humic acid extracted from an Andosol. Desorption of the adsorbed DNA using 4 different solutions-distilled water, 0.1 M NaCl, 0.1 M sodium phosphate buffer (pH 6.0), and 1% so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…This fraction of aqueous macrobial eDNA is likely to remain in suspension indefinitely until the DNA molecules degrade (Isao et al 1990). Water could advect eDNA in this state over long distances, especially in lotic systems, strong currents, and when extracellular/extraorganellar eDNA is protected via adsorption to other submicron particles (Saeki et al 2011). For example, transgenes from genetically modified corn were detected in river water up to 82 km downstream of a corn cultivation plot (Douville et al 2007), and plant DNA fragments as long as 1000 bp are detectable in groundwater (Pot e et al 2009).…”
Section: S T a T E A N D F A T E O F A Q U E O U S M A C R O B I A L mentioning
confidence: 99%
“…This fraction of aqueous macrobial eDNA is likely to remain in suspension indefinitely until the DNA molecules degrade (Isao et al 1990). Water could advect eDNA in this state over long distances, especially in lotic systems, strong currents, and when extracellular/extraorganellar eDNA is protected via adsorption to other submicron particles (Saeki et al 2011). For example, transgenes from genetically modified corn were detected in river water up to 82 km downstream of a corn cultivation plot (Douville et al 2007), and plant DNA fragments as long as 1000 bp are detectable in groundwater (Pot e et al 2009).…”
Section: S T a T E A N D F A T E O F A Q U E O U S M A C R O B I A L mentioning
confidence: 99%
“…This fraction of aqueous macrobial eDNA is likely to remain in suspension indefinitely until the DNA molecules degrade (Isao et al 1990). Water could advect eDNA in this state over long distances, especially in lotic systems, strong currents, and when free eDNA is protected via adsorption to other submicron particles (Saeki et al 2011). For example, transgenes from genetically modified corn were detected in river water up to 82 km downstream of a corn cultivation plot (Douville et al 2007), and plant DNA fragments as long as 1000 bp are detectable in groundwater (Poté et al 2009).…”
Section: State and Fate Of Aqueous Macrobial Ednamentioning
confidence: 99%
“…SOM is expected to increase the negative charge on minerals (Equation 1), leading to a mutual exclusion between SOM-rich allophane and negativelycharged phosphate groups of DNA. In contrast to Cai et al (2006b), Saeki et al (2011) showed that humic acid had a high affinity for DNA, hence the influence of SOM on DNA (and potentially aDNA) adsorption in Andisol is still debatable.…”
Section: Dna Adsorption On Allophanementioning
confidence: 86%